Kurdish Language Learning Tool in Serious Game - Hama Amin, Gulala Ali; Sharif, Karzan Hussein (Kurdistan Journal of Applied Research, 2020)
In this era, technology has a great impact on the educational system as they have on the other different areas of today’s life, for instance, smartphone devices are the best examples. Software technology vendors moving toward developing tremendous applications in the education field. However, the lack of applications that satisfy the ambition of those wishing to learn the Kurdish language is still an obstacle in this field, specifically the field of smartphone devices technology and gaming industry. Hence smartphone devices become user-friendly and necessary tools in every individuals’ life, as it is a multi-function device. In this paper we designed and implemented a smartphone application to learn the Kurdish language and improve vocabulary via a serious game. The application designed for android devices, enables users to learn and improve the Kurdish language. The application is also suitable for foreign people who desire to learn the Kurdish language. The system proposed in this paper introduces a smartphone application with an acceptable user interface for an exciting, interesting and challenging puzzle game at a time. The main goal is to learn Kurdish vocabulary using crossword puzzle, solving hidden words, find and circle the crossword in the puzzle solution in the context of a serious game.